2003
DOI: 10.1159/000070941
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Phone Dermatitis with Chromate Allergy

Abstract: Background: A patient with allergic contact dermatitis caused by hexavalent chromium plating on a cellular phone has already been reported. Objectives: This study described the clinical characteristics and results of patch tests in 8 patients with contact dermatitis possibly caused by handling a cellular phone. Patients: The 8 patients were 4 males and 4 females aged from 14 to 54 years. They each noticed skin eruptions after 9–25 days of using a cellular phone. All patients had erythema, and 7 had papules on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 8 publications
1
30
0
2
Order By: Relevance
“…20 The clinical relevance of metal content in cell phones leading to contact dermatitis has been suggested by several case reports (Tables 1 and 2), with 24 cases attributable to nickel allergy and the remainder secondary to chromates. 5,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The majority of these cases were characterized by pruritic, eczematous papules and plaques on the lateral cheeks and/ or preauricular area. The dermatitis typically presented unilaterally and in an irregular shape.…”
Section: Introductionmentioning
confidence: 99%
“…20 The clinical relevance of metal content in cell phones leading to contact dermatitis has been suggested by several case reports (Tables 1 and 2), with 24 cases attributable to nickel allergy and the remainder secondary to chromates. 5,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The majority of these cases were characterized by pruritic, eczematous papules and plaques on the lateral cheeks and/ or preauricular area. The dermatitis typically presented unilaterally and in an irregular shape.…”
Section: Introductionmentioning
confidence: 99%
“…In these reports, it is emphasized that "the prolonged contact" induces the reaction, as the cell phone material reacts with human sweat to become a contact allergen causing contact dermatitis. [6][7][8] In our patient also "the prolonged contact" was the main reason which induces the erythema and pigmentation as well. It is reported that during prolonged use of mobile phones, individuals feel a burning sensation in their auricles which might be associated with warming of the device.…”
Section: Discussionmentioning
confidence: 52%
“…Conversely, no measure was taken against chromate release by items in direct contact with the skin. Chromate allergic contact dermatitis of the auricle or the preauricular region has recently been described in patients using hexavalent chromium-plated cellular phones [7]. …”
Section: Discussionmentioning
confidence: 99%